Identifying interstitial lung disease associated chemicals by integrating transcriptome-wide association study and chemical-gene interaction networks: Chemical-gene interactions in lung disease - Wen, Changyu; He, Ting; Liu, Baishan (Cellular and Molecular Biology, 2023)
Interstitial lung diseases (ILD) comprise a heterogeneous group of lung disease characterized by common clinical syndromes and patterns of lung injury which poses growing burden on the health and social economic consequences. Its etiology remains elusive. By integrating transcriptome-wide association studies analysis of ILD and chemical-gene interaction networks implemented by CGSEA software, we systematically evaluated the association between ILD and 11,190 chemicals in this study. We detected several chemicals significantly associated with ILD (permutated empirical P values < 0.05). Briefly, a total of 56 chemicals were detected for ILD in lung tissue, 121 in whole blood respectively. Among the chemicals identified for ILD in lung tissue and whole blood, we found 7 common chemicals, including St. Thomas’ Hospital cardioplegic solution, cytarabine, ginsenoside Rg3, cholecalciferol, fluoxetine, oxidized-L-alpha-1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine and excitatory amino acid agonists. Our findings shed lights on the underlying impact of chemical exposure on the development and progression of ILD, which will pave the way for more effective prevention and treatment strategies, ultimately improving the health outcomes and quality of life of those affected by ILD.